Analysis of Natural Bioactive Compounds in Plant, Food, and Pharmaceutical Products Using Chromatographic Techniques - Shakeel, Faiyaz (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint titled "Analysis of Natural Bioactive Compounds in Plant, Food, and Pharmaceutical Products Using Chromatographic Techniques" deals with the separation and analysis of natural bioactive compounds in plants, foods, and pharmaceutical products. A growing tendency toward the discovery and use of natural bioactive compounds that are least harmful, have the fewest side effects, and fit the human body the most naturally has been noticed during the past few decades. As evidenced by the rise in recent studies on the therapeutic properties of plants, this trend has caused a return of healthcare professionals to nature and plants, but with a modern approach that specifically questions how plants help to heal humans and what their exact effects on the human body are. In order to identify and analyze natural bioactive compounds in plant, food, and pharmaceutical products, this reprint attempted to compile latest improvements, advancements, and analytical innovations in chromatographic techniques. In the last few decades, tremendous research on the analysis of natural bioactive compounds in plants, foods, and pharmaceutical products using wide range of chromatography techniques have been performed. This reprint has brought together prominent researchers who have explored a diverse applications range of chromatographic techniques in the extraction, separation, identification, and analysis of natural bioactive compounds.